Molecular mapping of the viral determinants of systemic wilting induced by a Lettuce mosaic virus (LMV) isolate in some lettuce cultivars - Krause-Sakate, R.; Redondo, E.; Richard-Forget, F.; Jadao, A. S.; Houvenaghel, M. C.; German-Retana, S.; Pavan, Marcelo Agenor [UNESP]; Candresse, T.; Zerbini, F. M.; Le Gall, O. (Elsevier B.V., 2005)
The isolate AF199 of Lettuce mosaic virus (LMV, genus Potyvirus) causes local lesions followed by systemic wilting and plant death in the lettuce cultivars Ithaca and Vanguard 75. Analysis of the phenotype of virus chimeras revealed that a region within the PI protein coding region (nucleotides 112-386 in the viral genome) and/or another one within the CI protein coding region (nucleoticles 5496-5855) are sufficient together to cause the lethal wilting in Ithaca, but not in Vanguard 75. This indicates that the determinants of this particular symptom are different in these two lettuce cultivars. The wilting phenotype was not directly correlated with differences in the deduced amino acid sequence of these two regions. Furthermore, transient expression of the LMV-AF 199 proteins, separately or in combination, did not induce local necrosis or any other visible reaction in the plants. Together, these results Suggest that the systemic wilting reaction might be Clue to RNA rather than protein sequences. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Lactuca sativa; agroinfiltration; infectious cDNA; necrosis; Potyvirus